1999
DOI: 10.1021/ja991613i
|View full text |Cite
|
Sign up to set email alerts
|

Mercury−Mercury Tunneling Junctions. 1. Electron Tunneling Across Symmetric and Asymmetric Alkanethiolate Bilayers

Abstract: Electron tunneling experiments involving Hg−Hg junctions incorporating two alkanethiolate monolayers are described. Formation of a symmetric junction (Hg−SC n −C n S−Hg) is accomplished by bringing in contact two small (3 × 10-3 cm2) mercury drop electrodes in a 5−20% (v/v) hexadecane solution of an alkanethiol. Formation of asymmetric junctions (Hg−SC n −C m S−Hg) and junctions containing n-alkane-3-thiopropanamide bilayers are also described. Tunneling currents in the junctions were measured for voltage bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
216
2
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(243 citation statements)
references
References 42 publications
(79 reference statements)
22
216
2
3
Order By: Relevance
“…in a break junction [10] or between mercury drops. [11] These methods provide insight in the transport of charges through the molecule, however, the results of such measurements are to a large extent determined by effects related to the contacts between electrodes and the molecule. In many cases the conductance can be considered to occur via a bridge-mediated superexchange mechanism in which the charge 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w O n l y 4 tunnels from one electrode to the other, without becoming localized on the molecular bridge.…”
mentioning
confidence: 99%
“…in a break junction [10] or between mercury drops. [11] These methods provide insight in the transport of charges through the molecule, however, the results of such measurements are to a large extent determined by effects related to the contacts between electrodes and the molecule. In many cases the conductance can be considered to occur via a bridge-mediated superexchange mechanism in which the charge 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w O n l y 4 tunnels from one electrode to the other, without becoming localized on the molecular bridge.…”
mentioning
confidence: 99%
“…Furthermore, many authors [44][45][46][47]58 also use alkylthiols with similar purities, and therefore our results are directly relevant to those studies, if not of general applicability. 3.3.…”
Section: Sfg Backgroundmentioning
confidence: 51%
“…10,17 FTIR investigation showed that the orientation of the alkanethiol SAMs on Au(111) surfaces are tilted ~ 30° from the surface normal. 18 Electronic transport through alkanethiol SAMs have also been characterized by STM, 19,20 conducting atomic force microscopy, [21][22][23][24] mercury-drop junctions, [25][26][27][28] cross-wire junctions, 29 and electrochemical methods. [30][31][32] These investigations are exclusively at ambient temperatureclearly useful -but insufficient for an unambiguous claim that the transport mechanism is tunneling (of course expected, assuming that the Fermi levels of the contacts lie within the large HOMO-LUMO gap).…”
Section: Progress and Accomplishmentsmentioning
confidence: 99%
“…[11][12][13] Previous work on Langmuir-Blodgett alkane monolayers 48 exhibited a significant impurity-dominated transport component, complicating the analysis. I(V) measurements on self-assembled alkanethiol monolayers have also been reported; [19][20][21][22][23][24][25][26][27][28][29]49 however all of these measurements were performed at fixed temperature (300 K) which is insufficient to prove tunneling as the dominant mechanism. To describe the transport through a molecular system having HOMO and LUMO energy levels, one of the applicable models is the Franz two-band model.…”
Section: Progress and Accomplishmentsmentioning
confidence: 99%